Front Line of Freedom : African Americans and the Forging of the Underground Railroad in the Ohio Valley. - Griffler, Keith P. (Ohio River Valley series., 2010)
The Underground Railroad, an often misunderstood antebellum institution, has been viewed as a simple combination of mainly white ""conductors"" and black ""passengers."" Keith P. Griffler takes a new, battlefield-level view of the war against American slavery as he reevaluates one of its front lines: the Ohio River, the longest commercial dividing line between slavery and freedom. In shifting the focus from the much discussed white-led ""stations"" to the primarily black-led frontline struggle along the Ohio, Griffler reveals for the first time the crucial importance of the freedom movement in